Ausentismo Laboral En La Hacienda Agrícola Bananera “LA MARGARITA - Vera Benitez, Karen Danessa (2017)
La Hacienda Agrícola Bananera la Margarita is a banana producer that was founded by Ing. Juan Antonio Larrea Taleb on October 22, 2000, in these farms grow the best fruits are sold brands such as: Rich Fruit, Probanna, Primadonna, Fruit Deli which have managed to make way in the international market for its quality. The company is dedicated to the production of organic and conventional bananas